Vegetable Variety Is a Key to Improved Diet Quality in Low-Income Women in California - Keim, Nancy L.; Forester, Shavawn M.; Lyly, Marika; Aaron, Grant J.; Townsend, Marilyn S. (Journal of the Academy of Nutrition and Dietetics, 2014)
Primary prevention education interventions, including those sponsored by the US Department of Agriculture for low-income families, encourage and support increases in vegetable intake. Promoting vegetable variety as a focal point for behavior change may be a useful strategy to increase vegetable consumption. A simple vegetable variety evaluation tool might be useful to replace the time-intensive 24-hour dietary recall. The purpose of our study was to determine whether vegetable variety is associated with vegetable consumption and diet quality among US Department of Agriculture program participants. Variety of vegetable intake and measures of total vegetable intake, diet quality, and diet cost were evaluated. Low-income, female participants (N=112) aged 20 to 55 years with body mass index 17.7 to 68.5 who were the primary food purchasers/preparers for their households were recruited from four California counties representing rural, urban, and suburban areas. Energy density and Healthy Eating Index-2005 were used to assess diet quality. Vegetable variety was based on number of different vegetables consumed per week using a food frequency questionnaire, and three groups were identified as: low variety, ≤5 different vegetables per week; moderate variety, 6 to 9 vegetables per week; and high variety, ≥10 vegetables per week. Compared with the low-variety group, participants in the high-variety group ate a greater quantity of vegetables per day (P<0.001); their diets had a higher Healthy Eating Index score (P<0.001) and lower energy density (P<0.001); and costs of their daily diet and vegetable use were higher (P<0.001). Thus, greater vegetable variety was related to better overall diet quality, a larger quantity of vegetables consumed, and increased diet cost.